Exploring Women’s Roles from Vedic to Modern Times: A Feminist Perspective - Bhatta, Damaru Chandra (The Outlook: Journal of English Studies, 2025)
This study critically explores the status of women across various historical eras from a feminist perspective, particularly through the lens of Simone de Beauvoir’s liberal feminist work The Second Sex. This paper analyzes the transformation of women's roles from the Vedic era to the modern era. Women's roles have evolved significantly from the Vedic era to the modern era, shaped by diverse influences including religious, social, and cultural factors. While ancient Hindu scriptures acknowledged gender equality, later eras imposed increasing restrictions on women's rights. However, the feminist movements have played in challenging these inequalities and advocating for gender justice. Employing a qualitative approach, this paper applies feminist theory, especially social constructionism and gender equality as outlined by Beauvoir. It examines historical texts, religious scriptures, and philosophical arguments from both Eastern and Western traditions to assess the shifting significance of women in different eras. Despite progress, women continue to face social and structural challenges. This paper emphasizes the need for gender equality through education, legal rights, and economic independence. By recognizing historical patterns and fostering mutual respect between genders, society can move toward a more inclusive and egalitarian future.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">